2014
DOI: 10.1021/jp409739b
|View full text |Cite
|
Sign up to set email alerts
|

Spin-State Effects on the Thermal Dihydrogen Release from Solid-State [MH(η2-H2)dppe2]+ (M = Fe, Ru, Os) Organometallic Complexes for Hydrogen Storage Applications

Abstract: Mössbauer spectroscopy, experimental thermodynamic measurements, and computational studies were performed to investigate the properties of molecular hydrogen binding to the organometallic fragments [MHdppe2]+ (M = Fe, Ru, Os; dppe =1,2-bis(diphenylphosphino)ethane) to form the dihydrogen complex fragments [MH(η2-H2)dppe2]+. Mössbauer spectroscopy showed that the dehydrogenated complex [FeHdppe2]+ adopts a geometry consistent with the triplet spin state, transitioning to a singlet state complex upon addition of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…The chemistry of ’ignoble’ metals is receiving increased attention, but this is an area where spin state problems and paramagnetism are more likely. For example, the reaction of [MH­(dppe) 2 ] + (M = Fe, Ru, Os; dppe =1,2-bis­(diphenylphosphino)­ethane) with H 2 to give trans -[MH­(H 2 )­(dppe) 2 ] + was probed by Fultz and co-workers who documented a triplet to singlet spin state transition on binding that accounted for the strong binding affinity for M = Fe. A number of Ni­(II)­(H 2 ) complexes have also been reported recently. , In paramagnetic (H 2 ) complexes, EPR data can provide useful information.…”
Section: Ignoble Metalsmentioning
confidence: 99%
“…The chemistry of ’ignoble’ metals is receiving increased attention, but this is an area where spin state problems and paramagnetism are more likely. For example, the reaction of [MH­(dppe) 2 ] + (M = Fe, Ru, Os; dppe =1,2-bis­(diphenylphosphino)­ethane) with H 2 to give trans -[MH­(H 2 )­(dppe) 2 ] + was probed by Fultz and co-workers who documented a triplet to singlet spin state transition on binding that accounted for the strong binding affinity for M = Fe. A number of Ni­(II)­(H 2 ) complexes have also been reported recently. , In paramagnetic (H 2 ) complexes, EPR data can provide useful information.…”
Section: Ignoble Metalsmentioning
confidence: 99%
“…Smoothing algorithms such as Savitzky-Golay [12] and Whittaker [13] smoothers are common for extracting peaks from noisy data, and are available in commercial spectrum processing software [14]. However, such techniques are often discouraged for Mössbauer spectroscopy due to an undesirable broadening of the peaks caused by these smoothers and the common presence of highly overlapping peaks within the spectra [15,16]. Advancements in processing power and memory management, however, have enabled researchers to revisit software algorithms as a means of improving spectrum characteristics, leading to improvements in the speed and operations of Mössbauer spectroscopy beyond what was available from hardware improvements alone.…”
Section: Introductionmentioning
confidence: 99%
“…Nuclear resonance vibrational spectroscopy (NRVS) has become a popular technique for elucidating the element-selective normal modes of appropriate Mössbauer isotopes. In previous work, we have shown that 57 Fe-NRVS can be utilized to observe Fe–H bending and Fe–H–Fe­(Ni) wagging modes in various model compounds as well as intermediate species of [NiFe] and [FeFe] hydrogenases. However, to date, the only reported Fe–H stretching modes were the bands around 1230/1430 cm –1 for a doubly bridging Fe­(μ-H) 2 Fe complex and at 1468/1532 cm –1 for a singly bridging Ni­(μ-H)Fe complex . To better gauge the feasibility for observing even higher frequency stretching modes expected for an iron-terminal hydride and dihydrogen, we have applied NRVS to examine a well-studied trans -[ 57 Fe­(η 2 -H 2 )­(H)­(dppe) 2 ]­[BPh 4 ] [dppe = 1,2-bis­(diphenylphosphino)­ethane] complex, , hereafter called 1 H H2 . As shown in Figure , our density functional theory (DFT) modeling of 1 H H2 produced an optimized structure that overlaps well with the X-ray diffraction result .…”
mentioning
confidence: 97%
“…21−23 However, to date, the only reported Fe−H stretching modes were the bands around 1230/1430 cm −1 for a doubly bridging Fe(μ-H) 2 Fe complex 24 and at 1468/1532 cm −1 for a singly bridging Ni(μ-H)Fe complex. 20 To better gauge the feasibility for observing even higher frequency stretching modes expected for an iron-terminal hydride and dihydrogen, we have applied NRVS to examine a well-studied trans-[ 57 Fe(η 2 -H 2 )(H)(dppe) 2 ][BPh 4 ] [dppe = 1,2-bis(diphenylphosphino)ethane] complex, 25,26 hereafter called 1 H…”
mentioning
confidence: 99%